Genetic polymorphisms and microRNAs: new direction in molecular epidemiology of solid cancer - Slaby, Ondrej; Bienertova-Vasku, Julie; Svoboda, Marek; Vyzula, Rostislav (Journal of cellular and molecular medicine, 2012)
MicroRNAs (miRNAs) are small non-coding RNAs, which regulate gene expression. Single nucleotide polymorphisms (SNPs) may occur in miRNA biogenesis pathway genes, primary miRNA, pre-miRNA or a mature miRNA sequence. Such polymorphisms may be functional with respect to biogenesis and actions of mature miRNA. Specific SNPs were identified in predicted miRNA target sites within 3' untranslated regions of mRNAs. These SNPs have a potential to affect the efficiency of miRNA binding to the target sites or can create or disrupt binding sites. Resulting gene dysregulation may involve changes in phenotype and may eventually prove critical for the susceptibility to cancer and its onset as well as for estimates of prognosis and therapy response. In this review, we provide a comprehensive list of potentially functional miRNA-related SNPs and summarize their importance as candidate cancer biomarkers.
Keywords: mikro RNA; Genetic Predisposition to Disease; Neoplasms; molekulární epidemiologie; 3' Untranslated Regions; zvířata; Humans; genetická predispozice k nemoci; genotyp; jednonukleotidový polymorfismus; Molecular Epidemiology; nádory; Genotype; MicroRNAs; lidé; 3' nepřekládaná oblast; Polymorphism, Single Nucleotide; Animals